EVALUASI PELAKSANAAN PROGRAM JAMINAN HARI TUA DI PT. PERKEBUNAN NUSANTARA II KEBUN SAWIT HULU KABUPATEN LANGKAT - NOVITA Marbun (Welfare StatE, 2013)
Every  employer  the have same right and chance to get job and word life with no differenfe one and the other. Because of government a law of employment makes. Dear of law number about 13 2003 is employers that have to realize the fundamental. It is used to improne dignity, prastice, pronsperious people. Guarantee old day programme guarantee and give protected  is used to for employers that should be pension. The pension time is one of horrible time employers old because their economy will  chance worse. Then government make a wise by give guarantee old day for employers. Based on the description of the background of the problem, then dirumuskanlah problem as follows: How Old Age Security Program Implementation at PT. Perkebunan Nusantara II kebun Sawit Hulu Kabupaten Langkat. Based on the formulation of the problem, it is the goal of this study was to determine the implementation of old-age insurance program in the PT. Perkebunan Nusantara II kebun Sawit Hulu Kabupaten Langkat. This examination is done at Hulticulture sawit hulu langkat. The examination user  descriptive examination by having 44 population of it. To obtain necessary data, thi research study using data collection technic and field study which consists of questionnaire and observation. program evaluation of guarantee old day pension at PT. Perkebunan Nusantara II has been done better based by data analysis. The programee evaluation can be seen by indicator sosialisation, understanding indikcator  and efektive time. Guarantee old day programme  is a good deelsion for pension time. Future this programme has to improved done well. Keywords : evaluation, guarantee old day.